The Effect of The Spelling Bee Game Method in Increasing Students’ Pronunciation of English Vocabulary - Titin Fatmawati; Marina Pakaya; Nur Wahidah Thayib Pido (Yayasan Adra Karima Hubbi, 2024)
Background. Children typically acquire their mother tongue and foreign languages, such as English, through interactive and engaging activities. Games like Spelling Bee create a relaxed, stress-free environment conducive to learning and vocabulary retention, which supports effective communication and reduces pressure on students. Purpose. The study aims to examine the effect of the Spelling Bee game on students' pronunciation of English vocabulary, focusing specifically on seventh-grade students. Method. This research employs a quasi-experimental quantitative approach using a time series design. Data collection techniques include a pretest, treatment (Spelling Bee game), and posttest. Data analysis was conducted through Normality and Hypothesis Tests (Shapiro-Wilk), with data processed using SPSS version 20. Results. The results reveal a significant improvement in students’ pronunciation of English vocabulary due to the Spelling Bee method. The mean score increased from 33.8 in the pretest to 226.9 in the posttest, with a significance value of 0.018 (<0.05), indicating that the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. This demonstrates the positive impact of the Spelling Bee game on pronunciation. Conclusion. The study concludes that the Spelling Bee method effectively enhances English vocabulary pronunciation among seventh-grade students. The findings strongly support the method's use in educational settings as a valuable tool for improving pronunciation skills and overall language proficiency.